Horses and rangelands: perspectives in Europe based on a French case study. (4th November 2015) - Jouven, M.; Vial, C.; Fleurance, G.
Abstract: The horse industry has soared in Europe in the last decades. This article analyses the existing and possible interactions between horses and rangelands, by taking horse feeding as well as environmental and socio‐economic issues into consideration. Due to the amount of recent data available for France, this country serves as a case study for the EU. Even though rangeland‐based feeding is common in traditional horse‐farming systems and still exists today on some pastoral farms, most horses are fed on conserved forage and concentrates, especially when the economic value of the horse is high. Scientific literature and recent field data suggest that rangelands can be used as the main feed source for mares and growing horses, providing not only nutrition but also a suitable environment for training and welfare. Horses can contribute to the sustainable development of rangelands, if they are well integrated into the local agricultural context and if horse grazing is carefully managed. To achieve this, a better integration of horses in the agricultural sector (from the field to research activities) is needed. An issue of utmost importance is the access of horse owners to land and technical support, taking into account that horses are herbivores similar to ruminants, as well as the peculiarities of the horse industry.